Visions of the tenement: Jews, photography, and modernity on the lower east side - Blair, Sara (2010)
Abstract Scholars have recently begun to focus on the problem of explaining a signal phenomenon: the preponderance of Jews (the so-called “people of the book”) in the development of modern photography. Against identitarian readings, this essay stresses the embeddedness of photography’s developing interests in a specific site in which both Jewishness and modernity were being made and remade: the variably iconic Lower East Side. Long imagined as a world apart, that space embodied the most profound and urgent paradoxes of historicity; it became a proving-ground for the powers of the camera to document new urgencies of social experience, and the experience of historicity itself. In particular, the built landscape and the iconography of its distinctive form, the tenements, became a resource for photographers of various affiliations for new stylistics and registers of response. Focusing on the difference the Lower East made to photographic practice, this essay aims to bring into view the importance of that site to the emergence of postwar photography, and to account more richly for the complex relations between Jewishness and visual practices.